Levilactobacillus brevis CD2 as a multifaceted probiotic to preserve oral health: results of a double-blind, randomized, placebo-controlled trial in healthy adults - Serena Altamura; Francesca Lombardi; Francesca Rosaria Augello; Antonella Barone; Mario Giannoni; Benedetta Cinque; Davide Pietropaoli (Journal of Translational Medicine)
Abstract Background A growing number of in vitro and in vivo studies suggest the application of probiotics as a natural approach to maintaining oral health. This double-blind, randomized controlled trial aimed to evaluate the efficacy of Levilactobacillus brevis CD2 (CNCM I-5566), a multifunctional probiotic frequently used in oral medicine, in preserving or improving several recognized oral health indicators. Methods Thirty consenting healthy adults were randomized to receive four lozenges per day of L. brevis CD2 probiotic (n = 15) or placebo (n = 15) over four weeks. Clinical parameters (full-mouth bleeding on probing (BoP) and plaque index (PI) scores) were recorded. Unstimulated saliva was collected to measure salivation rate, pH, and buffer capacity. Salivary biomarkers were analyzed, including glucose, D-lactate, and secretory immunoglobulins A (sIgA). Clinical and salivary parameters were assessed at baseline, after four weeks of intervention, and two weeks post-intervention. Wilcoxon rank-sum test and robust regression analysis were used for statistical comparisons. The possible mediating effect of PI on BoP changes was assessed. Results After four weeks, the probiotic group showed significant improvements in BoP and PI compared to baseline and placebo. The probiotic group had a higher salivation rate than baseline and placebo after four weeks of treatment and washout. While changes in salivary pH were not significant, buffering capacity increased in the probiotic group after four weeks of treatment and washout. Salivary glucose and D-lactate levels were lower in the probiotic group post-treatment and after washout. sIgA values increased and remained stable after washout in the probiotic group. No adverse effects were reported. Conclusions The treatment with L. brevis CD2 significantly improved clinical and salivary parameters, supporting its efficacy as a probiotic for oral health. Trial registration ClinicalTrials.gov , NCT06457724; Registered 7 June 2024 - Retrospectively registered; https://clinicaltrials.gov/study/NCT06457724?viewType=Table&page=452&rank=4512#study-overview .